The Price Distribution of Consumer Goods in Retail Markets - Kaldasch, Joachim (International Journal of Economics and Financial Issues, 2023)
Derived is an analytic dynamic model of the price distribution of consumer goods in retail markets. The stationary price distribution is established from the conservation equation of offered units and two simplifying assumptions. Under the condition that independent traders make small random price variations around a nearly constant supply price, the stationary price distribution of a good must have the form of a fat-tailed Laplace distribution. The standard deviation of the distribution is determined by the price volatility of the goods. Also, the price distribution of an ensemble of goods is established and applied to empirical data with good quantitative agreement.